Answer:
A. 6
Explanation:
To solve the equation 6x^2-2x+36=5x^2+10x, we can follow these steps:
Move all the terms to one side of the equation by subtracting 5x^2 and 10x from both sides:
6x^2 - 2x + 36 - 5x^2 - 10x = 0
Simplifying the left side:
x^2 - 12x + 36 = 0
Factor the quadratic expression on the left side of the equation:
(x - 6)(x - 6) = 0
Apply the zero product property, which states that if the product of two factors is equal to zero, then at least one of the factors must be zero:
x - 6 = 0
Solve for x:
x = 6
The solution to the equation 6x^2-2x+36=5x^2+10x is x = 6.